A Case Study Examining Fixed Versus Randomized Criteria for Treating a Child With Conduct Problems and Callous-Unemotional Traits. Issue 2 (2nd July 2016) - Waschbusch, Daniel A.; Bernstein, Melissa D.; Robb Mazzant, Jessica; Willoughby, Michael T.; Haas, Sarah M.; Coles, Erika K.; Pelham, William E.
ABSTRACT: Children with conduct problems and callous unemotional traits (CPCU) seem to show a decreased response to behavioral treatment. It was hypothesized that children with CPCU may respond differently to behavior therapy when the target behavior criteria are fixed a priori versus when they are randomly determined post hoc. A single-case study experiment was conducted as an initial step toward investigating this hypothesis. The study was conducted using a daily report card implemented in the context of an intensive behavioral summer treatment program. Results indicated that rates of negative behaviors were higher when rewards were delivered using randomly determined levels of target behaviors as compared to using fixed levels of target behaviors. Results suggest the importance of providing children with CPCU specific and predictable treatment goals when using contingency management procedures. Additional research that examines how children with CPCU react to components of behavioral treatment may help improve their response to behavior therapy.